Bacterial community structure and predicted function in the rhizosphere of wild and cultivated date palms: Effects of Fertilizers on Composition and Functionality - Dana A., Abumaali (2023)
This study investigated bacterial diversity in date palm rhizosphere and assessed the influence of different fertilizers on diversity using metagenomics. A total of 6356 Operational Taxonomic Units (OTUs) and 1164425 sequences were analyzed across 27 samples. The findings revealed variations in microbial community phylogeny among similar cultivars from different farms, except for the Khalas cultivar, suggesting minor influence of genotype on microbial community structure. Wild date palms exhibited more unique OTUs, in contrast, cultivated date palms had a higher number of OTUs and diversity. Moreover, different fertilizer treatments had varying effects on bacterial diversity. For example, organic and bio-organic fertilizers positively influenced specific bacterial groups, including delta-proteobacteria, acidobacteria-Gp3, Anaerolinaea, and Clostridia. Conversely, combining high concentrations of chemical fertilizers with other types did not show significant effects. Classes such as Bacilli, Nitrospira, Deltaproteobacteria, Spartobacteria, and Thermomacrobia exhibited high relative abundances in treatments with high chemical fertilizer concentrations. Our analysis revealed potential pathways related to carbon, nitrogen, phosphorus, phenol, sulfur, and antimicrobial compounds. Interestingly, these pathways and functions varied across different date palm cultivars. Our findings suggest that date palm cultivars shape the rhizosphere by selectively influencing bacterial communities consistently across other locations. These modulated bacterial communities can potentially provide enhanced benefits to the host. Importantly, this study was the first to investigate the soil bacterial diversity of wild date palms, giving valuable insights into the microbial community associated with this specific context.